Analogical Thinking in Theology - Taylor, W. S. (Scottish journal of theology, 1964)
Karl barth's emphasis on the Analogia Fidei, and the revival of interest in the Analogia Entis, both point up our contemporary concern about the place of analogical thinking in theology. A number of developments outside the field of theology proper also contribute to this concern about analogical thinking. A brief consideration of some of these developments may help to clarify one aspect of the significance of the Analogia Fidei.